Development of optical fibre sensors for real time measurements of nutrients in water - Erdody, Sandor (2022)
The research described in this thesis explores the possibility of the development of an optical fibre sensor (OFS) for the detection of nutrients in the water. The nutrients targeted were nitrites, ammonia and phosphates. The sensing platform to measure these targets was based on absorbance and long period grating optical fibre sensors. The long period grating sensors operating in the visible range for chemical measurements using sensitive dyes were also explored. For nitrite sensing, optical fibre was modified with the sensitive layer based on Brilliant cresyl blue (BCB) sensitive dye embedded into a base catalysed sol gel. The response of the dye to nitrite was studied in both free solutions and entrapped in sol gel matrix. The response and repeatability of the developed sensors in solution and sol-gel matrix were compared. The response was found to be not fully reversible in free solution, but reversible in base catalysed sol gel. The influence of pH as an interfering parameter was also compared with nitrite response and was proven to be opposite to the sensor's response, but a factor that needs to be taken into account in practical deployment. A ratio of two absorption peaks with opposite behaviour was used to analyse the dynamic response and repeatability. The BCB embedded sol-gel was deposited onto a U-shape and straight OFS via dip-coating. The sensor was found to give a repeatable response to nitrites in (deionised) DI water with 21.81 μM limit of detection (LOD) in the case of 0-50 μM detection range (DR), and 36 μM in case of 0-500 μM DR. However, the lifetime of the sensor appeared to be limited to few days, with complete insensitivity after 7 days of shelf life. Ammonia sensing was achieved using tetrakis-(4-sulfophenyl) porphyrin (TSPP) dye via OFS based on two different sensing platforms: U-shape and LPG OFS operating in the visible range. The response of TSPP dye to ammonia was examined in DI water, salt aqueous solution and seawater, and it was found to be not responsive in seawater, which makes the development of seawater sensors challenging. The TSPP was immobilised on the surface of the glass substrate using electrostatic layer by layer deposition of positively charged diazonium resin (DAR) – TSPP followed by UV treatment to create covalent bonding between DAR and TSPP. The ratio of intensity values at different wavelengths with opposite response behaviour was used to analyse the dynamic response and repeatability. 3 layer U-shape DAR-TSPP OFS sensitivity parameters to ammonia in DI water were 3.01 μM LOD at 0-10 μM detection range and LOD=25.94 μM 10-200 μM. The sensor showed a repeatable response. The research described in this chapter played a significant role in a sensor prototype, which was further industrially developed and is currently at its final stage of completion. The link between the complex refractive index and absorption governed by Kramers-Kronig relation opens the possibility of RI sensitivity in the ranges close to TSPP’s attenuation bands (eg. ~500 and 700 nm). In order to fabricate such LPG, with phase matching turning point (PMTP) close to TSPP’s attenuation bands, fibres with cut off wavelength in the visible wavelength range (488-633 for SM450 and 633-780 for SM600, both by Thorlabs) were chosen. In order to increase the photosensitivity of the optical fibre, they were loaded with hydrogen and UV-laser amplitude mask fabrication method was used to inscribe LPGs. The deposition and ammonia response of DAR-TSPP film was compared between „visible” and NIR LPGs, and only the „visible” LPG was found to be responsive to ammonia in DI water. The assumed explanation for this phenomenon is in the DAR/TSPP’s complex refractive index change behaviour in the visible range. The difference in the complex RI caused by DAR-TSPP ammonia response was calculated and analysed. Based on the response of the visible LPG modified with DAR/TSPP two different approaches to track ammonia response was proposed. One approach is intensity-based, - by taking the intensity ratio between 678.5 and 662 nm wavelengths (LOD~3.24 μM), the other by taking the sum of the PMTP central wavelength shift (LOD~4.81 μM). However, the proposed LODs are not superior to the existing detection techniques such as electrochemical, chromatographical, spectrophotometric and other optical detection techniques. The usage of the visible LPGs in combination with sensitive dyes is a novel approach that can be further investigated and significantly improved to increase sensor performance. Phosphate aqueous detector development was conducted via molecular imprinting. A molecularly imprinted polymer was synthesised based on N-allylthiourea monomers and PPA template. The template removal from MIP was evaluated via UV-VIS spectroscopy. The MIP film was deposited onto an LPG operating in reflection mode via dip-coating in a nitrogen atmosphere using UV enhanced dip coater setup. A novel approach to quantifying the response of an LPG OFS using the areas ratio of the PMTP was applied, where the ratio factor compensates for any intensity caused changes. Temperature compensation via thermocouple was performed. The test results show the response of LPG to phosphate concentration in water from 100 μM to 10 mM, however, the response is not linear and wasn’t able to be replicated with other similar attempts. Phosphate detection was also targeted with phosphate imprinted nanoparticles (called MIP materials) based on the unknown to author polymer provided by MIP Diagnostics Ltd using a U-shape sensor. The synthesised nanoparticles were claimed to be ~350 nm in size and coloure change was used to detect phosphates. 3 types of nanoparticles were designed with different binding functional groups (via silanization) and one type without any for matrix entrapped usage. MIP materials were examined for response to organic and inorganic phosphates in water and organic solvents as well as in their 50/50 mixture. It was established that water prohibits any response of the MIP materials. The scanning electron microscope(SEM) evaluations of MIP materials showed very few actual nanoparticles in the MIP materials. Filtration weighting showed only ~8-10.5% (depending on the type) of actual nanoparticles in the MIP materials provided. Due to a large amount of polymer residue, the deposition of the actual nanoparticles was problematic. SEM images of glass fibre coated with MIP materials confirm massive coverage of residues among rare nanoparticles. U-shape OFS coated with MIP grown directly on its surface in the facilities at MIP diagnostics was examined, unfortunately, none of the U-shapes found to be responsive to phosphates in water. In summary, the novelty of the work is in deploying VIS LPGs in combination with sensitive dye, first-time nitrites sensors with BCB sensitive due on optical fibre sensor, an attempt to develop MIP based sensor for phosphates on OFS.